Strategi Inovasi Usaha dan Pemasaran dalam Mempertahankan Eksistensi Usaha Djasmine Bordir di Era Modern - Fuadah, Rima Nurul (Journal of Economics and Business Research (JUEBIR), 2025)
This study aims to analyze the innovation and marketing strategies implemented by Djasmine Bordir to maintain its business existence in the modern era. The rapid growth of digital technology and changing consumer behavior require culture-based MSMEs to adapt and innovate to stay competitive. This research uses a qualitative descriptive method through observation, in-depth interviews, and literature studies conducted at Djasmine Bordir, Kudus Regency, Central Java. The findings reveal that Djasmine Bordir successfully integrates tradition with modernization through product innovations based on local wisdom, such as Kudus-inspired motifs, customization services, and contemporary fashion designs. In terms of marketing, digital strategies using social media, e-commerce platforms, and influencer collaborations are applied to expand market reach and strengthen brand image. Furthermore, the adoption of digital payment systems (QRIS) and participation in MSME exhibitions enhance competitiveness. In conclusion, Djasmine Bordir’s success in maintaining its existence is influenced by its adaptability to technological advancements and the implementation of innovative marketing strategies, enabling sustainable business growth amid modern challenges.